Levels of influence of parasites on the human immune system (Texas Journal of Medical Science, 2023)
Immunity is a protective reaction of the body. Currently, the study of the immune process is of great importance in medicine. Because the body is fighting against disease processes in the body through immune response reactions. This depends on the self-recovery and protection of the body. These are special protective cells (T and B lymphocytes, antibodies and antigens, through immunocomponents).